On One Co-Integration Issue of Trade Links of Azerbaijan, Russia, Belarus and Kazakhstan - E. G. Orudzhev; S. M. Huseynova (Статистика и экономика)
This article, based on annual data from 1994 to 2018, considers trade and economic processes between Azerbaijan, Russia, Belarus and Kazakhstan through the GDP integration indicators of Azerbaijan and foreign trade turnover with these countries.The purpose of the research. The purpose of the study is to find cointegration relationships between the studied macroeconomic indicators and correct application of the vector model of error correction to describe the equilibrium relationship between the considered data of intercountry interaction and to develop sound economically informative recommendations in the sphere of intercountry trade and economic interaction.Materials and methodology. Official statistics of the State Statistics Committee of Azerbaijan, scientific works of scientists-economists on the inter-country integration processes in the post-soviet region are used. Statistical methods of information processing are applied in relation to the empirical analysis of non-stationary time series of the studied statistical data, and correctly tested modern econometric methods and all the necessary econometric testing procedures are used to build co-integration relations and the vector model of error correction taking into account the effects of external shocks. All the calculations are made in Microsoft Excel and Eviews 8 application software packages.Results. The properties of applying the econometric methodology of studying the statistical relationship between multidimensional nonstationary time series are investigated. For this data, the authors' approach is to use the co-integration tool and the mechanism of vector error correction, which are practically not applicable by economists in Azerbaijan to date. A new specification of the model with respect to the logarithms of the source variables is defined. Based on the minimization of the mean square error, estimates of the model parameters are found. The Granger connection causality is investigated. The Johansen tests are implemented to find the cointegration area, after which the vector error correction model is built, which describes the long-term equilibrium relationship between the studied indicators and the path of returning to the equilibrium trajectory if it deviates from it. When modeling, we used all the necessary statistical procedures required to identify and evaluate the parameters of the model and verify its adequacy and the accuracy of short-term and long-term forecast values by applying Microsoft Excel and Eviews 8 tools.Conclusion. As a result of the study, econometrically sound recommendations are developed, which allow to conduct dynamic analyzes for effective state regulation of export-import operations between the four countries in order to balance the trade and improve the relevant inclusive parameters of the long-term sustainable development of these states.